2016
DOI: 10.1021/jacs.6b02176
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited State Relaxation of a Metalloporphyrin Revealed by Femtosecond X-ray Absorption Spectroscopy

Abstract: Photoexcited Nickel(II) tetramesitylporphyrin (NiTMP), like many open-shell metalloporphyrins, relaxes rapidly through multiple electronic states following an initial porphyrin-based excitation, some involving metal centered electronic configuration changes that could be harnessed catalytically before excited state relaxation. While a NiTMP excited state present at 100 ps was previously identified by X-ray transient absorption (XTA) spectroscopy at a synchrotron source as a relaxed (d,d) state, the lowest ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 88 publications
11
96
0
1
Order By: Relevance
“…(a) XANES spectraofN iPcOBu8, along with the enlarged pre-edger egion in the inset. [19] In our studyo f NiPcOBu 8 ,ak inetic trace taken at 8.342 keV (Figure 7), which tracks the intensity of the new 1s!4p z transition originating from the photoexcited state, showedasingle exponential decay with at ime constant of 525 AE 27 ps. EXAFS spectra of grounds tate (black) and constructed excited state (blue) are shownin( b) k-space and (c) R-space.T he R-space data is not phase-corrected.…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…(a) XANES spectraofN iPcOBu8, along with the enlarged pre-edger egion in the inset. [19] In our studyo f NiPcOBu 8 ,ak inetic trace taken at 8.342 keV (Figure 7), which tracks the intensity of the new 1s!4p z transition originating from the photoexcited state, showedasingle exponential decay with at ime constant of 525 AE 27 ps. EXAFS spectra of grounds tate (black) and constructed excited state (blue) are shownin( b) k-space and (c) R-space.T he R-space data is not phase-corrected.…”
Section: Resultssupporting
confidence: 50%
“…However,t he probed excited state of NiPcOBu 8 in this study revealed two pre-edge features arising at 8332 and 8334.5 eV, indicated by the difference spectrum as well as the extracted excited state spectrum.T his hints that the excited state probeda t1 00 ps after the 400 nm excitation is not ofaLMCT nature, but rather a( d,d) state in which both the 3d z 2 and 3d x 2 Ày 2 orbitals are singly occupied (Figure 6, right). [17][18][19] The blueshift of the 1s!4p z peak in the excited state also supported its assignment as a( d,d) state. [17][18][19] The blueshift of the 1s!4p z peak in the excited state also supported its assignment as a( d,d) state.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations